Tantangan Pendidikan di Era Disruptif: Ujian Online Berbasis Smartphone dengan Pengembangan Aplikasi xSIA - Resekiani Mas Bakar; Benny Enrico Leonard Panggabean; Eva Meizarra Puspita Dewi (Universitas Negeri Makassar, 2018)
Xsia21.xSIA.app was a digital archive system that simplified the lecturer in conducting, verifying and analysing the test result. The paperless method aimed to facilitate the participants to perform an examination without paper and pencil and for the lecturer to check the result as well. The participants in this study were 35 students. Participants filled four kinds of online assessment are questionare of paperless method, questionare of interview subject scale, true false test and multiple choice test. Test analysis used descriptive technique in xSIA web. The result of this study showed that positive responses enabled the participants show their positive emotion, share their opinion each other, receive the new experiences and represent their high interest. In addition, online test provided time efficiency and attractive design. The result of online test illustrated high score for most participants and proved that online test in Interview Subject offer a lot of advantages, either for students or lecturer.